2010
DOI: 10.1007/s10552-010-9540-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum CRP and IL-6, genetic variants and risk of colorectal adenoma in a multiethnic population

Abstract: Chronic inflammation, which is suspected to play a role in the development of colorectal cancer (CRC), has rarely been studied in colorectal adenoma. We investigated the inter-relationships of serum levels of the inflammatory proteins CRP and in IL-6, single nucleotide polymorphisms (SNPs) in the CRP (rs1205, rs1130864, rs1800947) and IL6 (rs1800795) genes, and lifestyle factors with colorectal adenoma in a sigmoidoscopy-based case-control study of 271 adenoma cases and 539 age-, sex-, and race/ethnicity-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 27 publications
7
59
6
Order By: Relevance
“…To our knowledge, only two previous studies have investigated the relationship between the circulating level of IL-6 and the risk of colorectal adenoma (16,17). Our findings for colorectal adenoma agree with the results of a cross-sectional study in which Kim and colleagues (16) found a positive association with the highest tertiles of IL-6 compared with the lowest tertiles.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…To our knowledge, only two previous studies have investigated the relationship between the circulating level of IL-6 and the risk of colorectal adenoma (16,17). Our findings for colorectal adenoma agree with the results of a cross-sectional study in which Kim and colleagues (16) found a positive association with the highest tertiles of IL-6 compared with the lowest tertiles.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, IL-6 levels were within the detectable range in all of our subjects using the high-sensitivity ELISA kit, allowing us to show differences in the levels of IL-6 between individuals with colorectal adenoma and controls at the low end of the concentration range. On the other hand, another case-control study of a multiethnic population showed no association between the serum concentration of IL-6 and colorectal adenoma risk (17). The present study population was rather smaller in size than those of these two previous studies, which included 873 participants (16) and 810 multiethnic participants (17), respectively.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…221 unrelated articles, 10 reviews and meta-analysis, 6 communications or letter, 7 single group design articles, 2 articles of controls were not healthy individuals and no data of two articles were excluded from the study in accordance with criteria of inclusion and exclusion. As a result, only 10 original studies (Wen et al, 2008;Motoyama et al, 2009;Pierce et al, 2009;Poole et al, 2009;Tsilidis et al, 2009;Chaturvedi et al, 2010;Ognjanovic et al, 2010;Slattery et al, 2011;Yang et al, 2011;Xu et al, 2013) were identified as eligible studies in our study. The detail flow chart of retrieval and identification and baseline characteristics of eligible studies were showed in Figure 1and Table 2 and Figure 2.…”
Section: Characteristics Of Eligible Studymentioning
confidence: 99%